Zinc (Zn) and Iron (Fe) Residues in Cattle Liver: A Comparative Study in Mining and Non-Mining Zones - Wulandari, Sitti Aisyah May; Jannah, Raodatul (Jurnal Biologi Tropis, 2026)
Laterite nickel mining activities in Southeast Sulawesi significantly contribute to environmental contamination, potentially leading to the bioaccumulation of heavy metals in free-grazing livestock. The liver, functioning as a primary metabolic organ, serves as a sensitive bioindicator for heavy metal exposure. This study aimed to analyze and compare the concentrations of essential heavy metals, Zinc (Zn) and Iron (Fe), in the liver of cattle reared in mining circum-areas (Sopura and Oko-oko) versus non-mining control areas (Toari and Watubangga). Liver samples were collected from 12 cattle (n = 3 per location). The samples were prepared using wet digestion and analyzed using Atomic Absorption Spectrophotometry (AAS). Data were analyzed using Independent Sample T-test and One-Way ANOVA followed by Tukey HSD post-hoc test. The results showed a significant difference (p < 0.05) in metal concentrations between mining and non-mining areas. The mining area of Oko-oko exhibited an extreme accumulation of Iron (Fe), reaching 1,803.40 ± 48.64 mg/kg, which is significantly higher than the control area of Watubangga (47.69 ± 1.94 mg/kg). Zinc (Zn) levels were also significantly higher in mining areas (21.88–24.22 mg/kg) compared to non-mining areas (2.97–8.30 mg/kg). There is a strong correlation between mining activities and the bioaccumulation of Zn and Fe in bovine liver. The extreme iron levels detected in the mining zone suggest a potential health risk for consumption, necessitating the implementation of depuration strategies and stricter food safety monitoring in the affected regions.